Rational design of peptides with enhanced antimicrobial and anti‐biofilm activities against cariogenic bacterium Streptococcus mutans. (10th July 2019) - Liang, Dongsheng; Li, Huanying; Xu, Xiaohu; Liang, Jingheng; Dai, Xingzhu; Zhao, Wanghong
Abstract: Streptococcus mutans ( S. mutans ) is known to be a leading cariogenic pathogen in the oral cavity. Antimicrobial peptides possess excellent properties to combat such pathogens. In this study, we compared the antimicrobial activity of novel linear reutericin 6‐ and/or gassericin A‐inspired peptides and identified LR‐10 as the leading peptide. Antibacterial assays demonstrate that LR‐10 is more active against S. mutans (3.3 μM) than many peptide‐based agents without resistance selection, capable of killing many oral pathogens, and tolerant of physiological conditions. LR‐10 also presented a faster killing rate than chlorhexidine and erythromycin, and appeared to display selective activity against S. mutans within 10 s. S. mutans is usually encased in plaque biofilms. Biofilm inhibitory assays indicated that LR‐10 had excellent inhibitory effect on the biofilm formation of S. mutans and biofilm‐encased cells in vitro at low concentrations (6.5 μM). Consistent with most peptides, LR‐10 kills S. mutans mainly by disrupting the cell membranes. Notably, both hemolytic activity assays and cytotoxicity tests indicated that LR‐10 could keep biocompatible at the effective concentrations. Hence, LR‐10 could be a good candidate for clinical treatment of dental caries. Abstract : A series of LR‐1 derivatives were modified from reutericin 6 and/or gassericin A. LR‐10 was indentified as the most promising peptide‐based peptide in terms of its inhibitory effect on Streptococcus mutans planktonic cultures or biofilms. The results show that LR‐10 could be a good candidate for clinical treatment of dental caries.